Penguatan Ketahanan Masyarakat di Era Pandemi Covid-19: (Pengabdian Masyarakat di Desa Sine, Kecamatan Sragen, Kabupaten Sragen) - Siti Rokhaniyah; Sinta Sinta (Journal of Community Development, 2021)
The Covid-19 pandemic has a significant impact on all aspects of life, both in the fields of education, health, religion, economy, tourism, and others. In terms of education, the Covid-19 pandemic has inspired the birth of an online learning policy. The economic aspect has also stalled, due to the enactment of Large-Scale Social Restrictions (PSBB) so that various conventional economic transactions have been significantly transformed into the online system. The religious sector has also been affected by changes, due to a reduction in the capacity of places of worship. Based on the results of participant observation, it was found that changes in the life order due to the Covid-19 pandemic also occurred in Village of Sine, Sragen, Central Java. Some of the problems that arise in the community are problems in the field of education, how to overcome difficulties in implementing online learning, in the religious field, the termination of TPA (Al-Quran Education Park) and other religious activities such as recitation, while in the health sector, how the community's efforts to increase resilience during a pandemic are not yet aware of the importance of washing hands correctly and wearing masks. The most vital aspect is the economy, where most people work as traders and factory workers who are forced to stop working. In order to reduce these difficulties, community service activities were carried out that focused on several identified problems. Among the activities that have been carried out are learning assistance to children, organizing TPA for children, organizing socialization on preventing the spread of Covid-19 and providing entrepreneurial motivation for people affected by Covid-19. For the implementation of this community service activity, the residents of Sine Village feel very helped, and hope that it will be sustainable.